2021
DOI: 10.3390/ma14195788
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light-Activated Riboflavin Phosphate Promotes Collagen Crosslinking to Modify the Properties of Connective Tissues

Abstract: Reduced amounts of collagen and fragmented collagen fibers are characteristics of aging skin. Recently, user-friendly, at-home personal aesthetic devices using light-emitting diode (LED) light have been used for cost-effective and safe skin improvement. However, to dramatically improve the skin via collagen repair, we need to develop an LED-responsive photosensitizer. Corneal collagen crosslinking uses ultraviolet light to activate riboflavin phosphate (RFP) and is used in ophthalmology. RFP is a biocompatible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…UV irradiation with a weak intensity of 3 mW cm −2 is applied for a period of approximately 30 min. Kang et al demonstrated that RFP-induced crosslinking increased the Young’s modulus and tensile strength of skin tissues by approximately three times by applying the same procedure to skin collagen as that for corneal collagen [ 46 ]. Blue light is safer than UV light when applied to the skin; therefore, visible light with a wavelength of 450 nm was employed.…”
Section: Riboflavin-induced Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…UV irradiation with a weak intensity of 3 mW cm −2 is applied for a period of approximately 30 min. Kang et al demonstrated that RFP-induced crosslinking increased the Young’s modulus and tensile strength of skin tissues by approximately three times by applying the same procedure to skin collagen as that for corneal collagen [ 46 ]. Blue light is safer than UV light when applied to the skin; therefore, visible light with a wavelength of 450 nm was employed.…”
Section: Riboflavin-induced Photochemistrymentioning
confidence: 99%
“…Similar to the cornea, skin tissue is exposed to the environment, and collagen is a significant component of the dermis. Applying RFP-mediated photochemistry to skin tissue increases its elasticity and strength [ 46 ]. For practical applications, further studies are required to achieve the delivery of sufficient amounts of RFP to the dermal layer for photochemistry.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Collagen glycation also proved to be an effective stiffening method, although it is time consuming [ 81 , 82 ]. Finally, the use of ultraviolet crosslinking in the presence of riboflavin possesses the advantage of being a simple and effective method that may also act on a local scale: by using light masks that spatially filter light transmission, it is possible to create patterns or gradients of crosslinked fibrils in the gel [ 83 , 84 ]. Light irradiation, especially in the UV range, may induce cytotoxic effects.…”
Section: 3d Fibrillar Collagen Gelsmentioning
confidence: 99%
“…Visible light-mediated photo-cross-linking initiated the reaction by irradiating blue light to convert riboflavin phosphate (RFP), a vitamin B derivative, into an excited state. RFP is used as a photoinitiator because of its capacity to absorb light. After being exposed to light, RFP gets excited and takes on electrons from electron donors, thus, transferring their energy. The intermediate receiving the energy oxidizes substrates, such as biomolecules, and this sequential reaction is called RF-mediated oxidation .…”
Section: Introductionmentioning
confidence: 99%